Culture as a constitutive dimension of social life: theoretical proposals of Raymond Williams and Clifford Geertz. Convergences and divergences - Montero Reyes, Yilena (Southern perspective / Perspectiva austral, 2024)
Clifford Geertz, in his seminal work “The Interpretation of Cultures” (1973), proposes that culture should be understood as a system of symbolic meanings that are interpreted rather than seeking laws through experimentation. Geertz stresses that culture is a web of meanings and that anthropology should focus on the interpretation of these symbolic meanings. His semiotic perspective holds that culture is a text that people read and create to make sense of their experiences. On the other hand, Raymond Williams criticizes the base-superstructure model, arguing that culture is an active meaning-making process that permeates all social actions. Williams argues that cultural practices are both social and material and that the economy is intrinsically linked to culture. Both authors agree that culture is fundamental to understanding social actions and history. Geertz focuses on symbolic interpretation, while Williams stresses the relationship between culture and economics, proposing a view of cultural materialism that incorporates cultural production as an essential part of social life. Culture, according to Williams, must be seen as an integral process that includes conflict and change, and not simply as isolated products of society. In abstract, the work of Geertz and Williams provides a profound understanding of culture as a web of symbolic meanings that must be interpreted in order to understand social dynamics and historical processes